Development of Waginem (Morning and Evening Time) Mathematics Teaching Aids for Time Materials - Afriyani, A; Shalikhah, Norma Dewi (Prosiding University Research Colloquium, 2021)
This research is motivated by the lack of teaching aids for time material at school. The purpose of this study was to develop Waginem (Morning and Evening Time) teaching aids to make it easier for students to understand the time material in learning mathematics. The type of research is development research (R&D) which consists of several stages, namely finding potentials and problems, gathering information, product design, design validation, design improvement, and product testing. The product trial subjects were students of class II MI Muhammadiyah Paremono Magelang. The instrument used is a questionnaire sheet to determine the validity and responses of students to teaching aids. The results showed that Waginem's teaching aid was very valid with a score of 89.5% and student responses scored 97.2% with very good criteria. So that the conclusion is that Waginem's teaching aids are suitable for use in time material learning mathematics for grade II elementary school students.